Non-Linear Impact of Growth Opportunity and Firm Size on the Capital Structure - Kim Sung Suk; Rita Juliana; Irwan Adi Ekaputra (Jurnal Keuangan dan Perbankan, 2018)
One of the focuses on capital structure studies is to identify economic forces influencing corporate capital structure. We investigated the non-linear effects of the firm-specific factors to the leverage of the firm of the US-listed firms. In the partial-adjusted model, growth opportunity and the size of the firm had non-linear effects on the leverage of the firm. Growth opportunity showed quadratic effects on leverage with a negative linear term but a positive quadratic term. It meant if the growth opportunity of a firm reached a certain level, fund providers can relatively detect it and subsequently causes a decrease in asymmetric information. This detection of ample growth opportunity will increase the accessibility of external funding. Firm size also exhibits quadratic effects on leverage with a positive linear term but a negative quadratic term. In other words, if the firm size as a proxy of various omitted variables was imminent, the financial market has been applied the diversification discount that will decrease the accessibility of external funding.JEL Classification: G32, D92DOI: https://doi.org/10.26905/jkdp.v22i4.2402